Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Pada Kopi Magma di Krukut Kota Depok Jawa Barat - Dani Maulana; Reza Khairul Hadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the effect of price and promotion on purchasing decisions on Magma Coffee in Krukut, Depok City, West Java. both partially and simultaneously. The method used is quantitative. The sampling technique used is probability / random. Sampling uses a random selection process (random sampling / probability) and gives each member of the population the same opportunity to be taken as a sample and obtained a sample in this study totaling 100 respondents. The results showed that Price (X1) and Promotion (X2) had a significant effect on Purchasing Decisions by obtaining the regression equation Y = 5.788 + 0.381X1 + 0.460X2, The value of the correlation coefficient or the level of influence between the independent variable and the dependent variable is obtained at 0.758, meaning that it has a strong relationship. The coefficient of determination is 0.574, it can be concluded that the Price and Promotion variables affect the Purchasing Decision variable by 57.4%, while the remaining 42.6% is influenced by other factors that were not studied. Partial hypothesis testing (X1 to Y) it is known that the tcount value is 8.899> ttable 1.984 with a significant level of 0.000 <0.05, so Ho is rejected and Ha is accepted, indicating that there is an effect of price on purchasing decisions at Magma Krukut Coffee Shop, Depok City. And partial test (X2 to Y) it can be seen that the tcount value is 9.915> ttable 1.984 with a significant level of 0.000 <0.05, so Ho is rejected and Ha is accepted, indicating that there is an effect of Promotion on Purchasing Decisions at Magma Krukut Coffee Shop, Depok City. Meanwhile, for the simultaneous test, the value of Fcount> Ftable or (65.386> 3.090) is obtained, this is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). Thus, H0 is rejected and H3 is accepted, this shows that there is a simultaneous significant influence between Price and Promotion on Purchasing Decisions on Magma Coffee in Krukut, Depok City, West Java.